Reading and shaping medieval cartularies : multi-scribe manuscripts and their patterns of growth : a study of the earliest cartularies of Glasgow Cathedral and Lindores Abbey /: multi-scribe manuscripts and their patterns of growth : a study of the earliest cartularies of Glasgow Cathedral and Lindores Abbey. (2020) - Tucker, Joanna, 1990-
No abstract available